STRATIGRAFI DAN BIOTA JURA KEPULAUAN MISOOL, INDONESIA DAN KORELASI INTERREGIONAL DAN GLOBALNYA - Fauzie Hasibuan (Jurnal Geologi dan Sumberdaya Mineral, 2009)
The Jurassic fauna of Misool Archipelago is very similar to Sula Islands on the basis of bivalve content, but it differs from Sula Islands in that good ammonite assemblages which replaced by assemblages of belemnites. The fauna of Misool Archipelago can also be correlated with Papua is on the basis of ammonite fauna such as Fontannesia killiani. Misool Archipelago fauna is also correlable with those of the European Alps, North America, Chile, Argentina, New Zealand, Northwestern Australia, North and South Tibet, Himalaya, etc. However, some areas correlation is based only on a few species and sometimes only on cosmopolitan genera.Â Keywords: Jurassic, Misool Archipelago, ammonites, bivalve, interregional and global correlationÂ